Sound Bites: Music as Violence - John Morgan O’Connell (Transposition)
In this essay, I interrogate the ideas that concern music and violence which are presented by scholars in this Transposition special issue. Although each article is very different, common themes emerge. I interpolate these with reference to my own research into the sounds of music in the Gallipoli Campaign (1915-1916). Following Nikita Hock, I examine the notion of metaphor as it relates to underground hideouts in a war zone. Following Victor A. Stoichita, I look at how music affords distinctive pathways in the fulfilment of or disengagement from acts of violence. Following Sarah Kay, I examine the ways in which contrafactum helps clarify the ambivalent positionality of Allied recruits in a foreign campaign. I also refer to Kay’s notion of “extimacy” when interpreting expressionist representations of warfare in the Dardanelles.